2020
DOI: 10.1002/tqem.21710
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the urban space: Assessment of residents’ experience and satisfaction with the legibility of Ibadan municipality, Nigeria

Abstract: Using urban legibility elements, this paper examined residents’ experience and satisfaction with navigation in Ibadan metropolis. This was with a view to suggesting policy response to enhance the livability and sustainability of the city and others with similar background. Five local government areas make up Ibadan municipality and comprise three residential areas (core, transition, and suburban). One ward was randomly selected in each residential zone of the city. A total of 14,269 residential buildings were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Findings obtained from cognitive studies in urban spaces revealed that the most important factors in shaping cognitive maps of children consist of parks, playgrounds, green spaces and entrances [48]. Studies also indicated that the integration of urban legibility elements should enhance the level of navigation, livability, and sustainability in urban spaces [49].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Findings obtained from cognitive studies in urban spaces revealed that the most important factors in shaping cognitive maps of children consist of parks, playgrounds, green spaces and entrances [48]. Studies also indicated that the integration of urban legibility elements should enhance the level of navigation, livability, and sustainability in urban spaces [49].…”
Section: Literature Reviewmentioning
confidence: 99%